2009
DOI: 10.1007/s10517-009-0436-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Method for Measurement of Acetylcholinesterase Activity

Abstract: Fluorescence intensity of thioflavin T fluorogenic label increased significantly as a result of formation of enzyme-inhibitory complex with acetylcholinesterase of human blood erythrocytes. Thioflavin T is a reversible inhibitor, selectively reacting with acetylcholinesterase. Thioflavin T fluorescence intensity is proportional to acetylcholinesterase activity for the studied interval of enzyme activities. A rapid fluorescent method for measuring acetylcholinesterase activity is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Blood acetylcholinesterase (BChE) activity was measured on posttreatment days one and seven, by the method described by Antokhin et al [44]. In the presence of BChE, the hydrolysis of Ach and production of acetic acid decreases the pH of the reaction mixture.…”
Section: Blood Acetylcholinesterase Activitymentioning
confidence: 99%
“…Blood acetylcholinesterase (BChE) activity was measured on posttreatment days one and seven, by the method described by Antokhin et al [44]. In the presence of BChE, the hydrolysis of Ach and production of acetic acid decreases the pH of the reaction mixture.…”
Section: Blood Acetylcholinesterase Activitymentioning
confidence: 99%
“…Thioflavine T was chosen for the development of this biosensor because of the high fluorescence inten sity of its complex with the recombinant AChE of human erythrocytes, which is higher than the fluores cence intensity of the initial thioflavine T at λ ~490 nm upon excitation with radiation at λ = 448 nm by a fac tor of 1000 [34]. A considerable increase in the fluo rescence intensity of thioflavine T in the presence of the AChE of human erythrocytes was observed by Antokhin et al [35]. Scheme 2 shows the structural formula of thioflavine T. The fluorescence intensity of the discussed optical biosensor under the action of the insecticide (~50 nM) diethyl (3,5,6 trichloropyridin 2 yl) phosphate or dichlophos decreased by 50% rela tive to the initial fluorescence intensity of the optical biosensor [33].…”
Section: Analysis Of Promising Trends In the Development Of Up To Datmentioning
confidence: 99%
“…The three-dimensional structure of acetylcholinesterase (Figure ) reveals a deep narrow gorge that contains two ligand binding sites: a peripheral site (P-site) near the gorge entrance and an acylation site (A-site) at the base of the gorge . Thioflavin T (ThT), a fluorescent probe widely used as a test for amyloid fibril formation, binds selectively to the AChE peripheral site, wherein the ThT fluorescence intensity increases significantly. The proved proportionality of the dye’s fluorescence intensity to AChE activity led to the elaboration of a rapid fluorescent method for determination of AChE activity using ThT . Furthermore, it was shown that with binding of another ligand to the A-site in a ternary complex and initiation of a change in the local AChE conformation at the peripheral site, the enhanced fluorescence of ThT is quenched in 1.5 to 4-fold. ,, This fact allows ThT to be used as a reporter for ligand reactions at the AChE acylation site.…”
Section: Introductionmentioning
confidence: 99%
“…14−16 The proved proportionality of the dye's fluorescence intensity to AChE activity led to the elaboration of a rapid fluorescent method for determination of AChE activity using ThT. 17 Furthermore, it was shown that with binding of another ligand to the A-site in a ternary complex and initiation of a change in the local AChE conformation at the peripheral site, the enhanced fluorescence of ThT is quenched in 1.5 to 4fold. 10,16,18 This fact allows ThT to be used as a reporter for ligand reactions at the AChE acylation site.…”
Section: Introductionmentioning
confidence: 99%